HUSBAND SUPPORT IN PREGNANT WOMEN WHO TAKE FOLAMIL SUPPLEMENTS FOR INCREASING HEMOGLOBIN LEVELS: A LITERATURE REVIEW - Irmawati Irmawati; Andi Nilawati Usman; Mardiana Ahmad; Nur Aliya Arsyad (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Folic acid deficiency in pregnancy will cause impaired maturation of erythrocyte nuclei, resulting in the appearance of red blood cells with abnormal shapes and sizes referred to as megaloblastic anemia, further impaired folic acid metabolism will cause impaired DNA replication and cell division processes, and this will affect the work of all cells of the body, including in iron metabolism. Objectives: This study aims to determine the effect of husband support on pregnant women who consume phthalate supplements for increased hemoglobin levels. Design: This research design is a systematic review to find and review articles from databases and theories that are descriptive. Data Sources: Search for articles using the old version of the Mendeley application by entering the keyword "folic acid in pregnant women with inclusion criteria, namely the year of publication 2017-2021, English, full text and open access. There were 11 articles that were willing to be reviewed based on the inclusion criteria. Review Methods: Systematic review method by filtering on the Mendeley website based on inclusion criteria, then collected and made a summary of the journal including the name of the researcher, year of publication of the journal, research title, method, and summary of results or findings. Summary of research journals are entered in table 1. Results: From the search for articles, 4,463 articles were found. After filtering 9 eligible articles based on inclusion criteria, it was found that the level of folic acid consumption for pregnant women was still very low. Husband's support from the family can encourage pregnant women to be more enthusiastic in dealing with the changes that occur during pregnancy, including maintaining a healthy pregnancy through increased pregnancy visits and consumption of folic acid supplements. Pregnant women who receive attention and support from their husbands and families are more likely to accept and follow the advice given by health workers compared to pregnant women who receive less attention and support from their husbands and families. Conclusion: Husband support in pregnant women who take Folamil supplements for the improvement of Haemoglobin is an important factor and has a very large influence on the health of pregnant women, so cooperation is needed between health workers and the family, especially the husband, in order to improve the health status of pregnant women.